Particular features of the immune status in microbial eczema and erysipelas patients: a therapeutic method - G. M. Zinatulina; E. V. Fayzullina; V. H. Fazyilov; D. A. Vasilkin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal of the study. To study particular features of the immune status in microbial eczema and erysipelas patients in the process of a complex immune modulating therapy with Xymedone®. Materials and methods. the study involved 45 microbial eczema patients and 31 patients with a combined form of microbial eczema and erysipelas (the study group) and healthy subjects (60 and 50 subjects). All of the subjects underwent immunology examinations of their cell and humoral immunity prior to and after the pathogenetic treatment with Xymedone®. The traditional therapy of a combined course of microbial eczema and erysipelas comprised the following basic treatment: third-generation cephalosporins (ceftriaxone): 1.0 g a day for 10 days; second-generation antihistamine drugs (peroral loratadine 10 mg once a day for 10 days) and ascorbic acid 0.5 g a day for 14 days. topical treatment comprised antiseptic agents (furacilin solution 1:1000) at the acute stage, emulsions and creams (depending on the disease stage): topical mometasone furoate 0.1% twice a day for 14 days. The patients receiving Xymedone were treated in the dose of 0.25 g, one pill tree times a day for 14 days. The patients underwent an immunology study using the Sysmex Corporation XT2000 automated analyzer at the CityLab laboratory centers in the city of Kazan. Key findings. Prior to the pathogenic therapy, a high level of CD4 (T helpers) and reduced level of the immunoregulatory index (T helpers to T suppressors ratio) (IRI) was revealed in the microbial eczema patients. Ig А and Ig G concentrations were reliably increased. According to a study of immunology indices, the pathogenic therapy using Xymedone® normalized the number of peripheral blood leucocytes and reliably increased the IRI (p < 0.001) in 45 microbial eczema patients. Prior to the pathogenic therapy, a reduced level of CD3 and CD4 cells was revealed in patients with a combined form of microbial eczema and erysipelas; the levels of CD8 and NK cells (CD16) were also reduced. Ig А, Ig M and IgG concentrations were reliably reduced. According to a study of immunology indices, the pathogenic therapy using Xymedone® increased the concentration of CD3 and CD4 cells. Conclusion. Xymedone®, an immune modulating drug, administered as a part of a combination therapy of microbial eczema patients and patients with a combined form of microbial eczema and erysipelas is a form of supplementary pathogenic I therapy; the treatment improved the cellular and humoral immunity indices.